Biological fluid : surface interactions in detection and medical devices /: surface interactions in detection and medical devices. (2016) - Thompson, Michael, 1942-; Blaszykowski, Christophe; Sheikh, Sonia; Rodriguez-Emmenegger, Cesar; Pereira, Andres de los Santos
No abstract available